A migração laboral no Mercosul a partir da análise dos acordos sobre residência: entre ousadia e timidez - Gruppelli, Jaqueline Lisbôa (2008)
Even though it has been a little more than 15 years since the establishment of Mercosur and, along with it, the intention to strengthen the process of regional integration, through the commitment of the member countries - Argentina, Brazil, Paraguay and Uruguay of having their legislations in conformity, there are still many gaps which are easily visible creating obstacles for the social integrations of the peoples involved. Among these deficiencies, some endorsed documents along the history of Mercosur are directed to the protection of human rights and, consequently, to the social integration. However, some still lack effective commitment previously agreed by the member countries. Therefore the present paper becomes important as it is understood that the strengthening of the regional integration is not solely base don the economical trades between the countries. Moreover, due to the bordering permeability created with the Mercosur, the integration enlarges its reach with the human movement and the consequences produced by it. In this scenario, the present paper aims at investigating if the recent Agreements on Residence for Natives from the Mercosur member Countries discipline the human right to work of the immigrants from Mercosur. In order for that to happen, in a first moment we approached the necessity of interaction between the social and economical integration, from the protection of the human rights of the immigrant workers from the Mercosur countries. After that, the effectiveness of the Agreements on Residence and the repercussions for the social integration were analyzed, both in terms of perspectives of advancing as well as in terms of the stagnation of this integration. Finally, an investigation concerning the Mercosur working jurisdictions has been made previous to the Agreements being studied here, concerning the entailing judicial powers as well as the impact on the immigrant workers native from the Mercosur countries. Concluding, base don the analysis made, it is suggested a bigger effort from the member countries in relation to the working social norms endorsed which, theoretically, demonstrate being quite satisfactory, but lack real effectiveness in the Mercosur area.